(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2022)
In the history of the 19th-century archaeological research in Calvatone-Bedriacum, Father Luigi Luchini, born in Milan but lived for most of his life in the territory of the Diocese of Cremona, played a central role. The Ala Ponzone Civic Museum keeps interesting archival documents to reconstruct the first findings of the vicus and the vicissitudes of the collection that originated from them.